Parasitism capacity of Trichogramma pretiosum on eggs of Trichoplusia ni at different temperatures (Acta Scientiarum. Agronomy, 2014)
Trichogramma spp. are egg parasitoids of various pest species of Lepidoptera including Trichoplusia ni, an important pest of plants in the genus Brassica. Of the climatic conditions that can impair Trichogramma spp. parasitism capacity, the temperature is critical. Thus, the objective of this research was to evaluate the parasitism capacity of Trichogramma pretiosum on eggs of T. ni at 18, 21, 24, 27, 30, and 33ºC; 70±10% RH; and 12/12 hours photophase (L/D). Fresh eggs of the host moth were offered to T. pretiosum daily. The parasitism rate varied between 8 and 11.4 eggs/female at the temperatures evaluated for the first 24 hours. The highest number of parasitized eggs per female occurred at 24ºC (53.0 parasitized eggs/female). The period of parasitism and the mean longevity of females were inversely related to the temperature. Temperature heavily influences the parasitism rate of T. pretiosum on eggs of T. ni, and the best overall performance of the parasitoid occurs from 24 to 27ºC.